Kingella kingae Keratitis in a Child with Underlying Vernal Keratoconjunctivitis - Salim, Nurul Laila; Chai, Khai Siang; Ahmad Tajudin, Liza Sharmini; Ismail, Shatriah (Hindawi Publishing Corporation, 2017)
Kingella kingae had rarely been reported as a causative organism for corneal ulcer and had not been described before in vernal keratoconjunctivitis (VKC). Generally regarded as commensals of respiratory tract particularly in young children, it had however been isolated fromthe corneal ulcer scraping of both adult and children.We report a case of bacterial ulcer with isolation of Kingella kingae from the corneal scraping in a young child with underlying VKC.